A Novel Approach for Channel Estimation In MIMO-OFDM System Using The Efficient Pilot Patterns (International Journal of Engineering and Computer Science, 2014)
A novel approach is presented in this work to efficient pilot patterns estimation as well as channel estimation in multiple input-multiple output orthogonal frequency division multiplexing system. In our proposed work, we exploit the basic orthogonal property of unitary matrix based on scattered pilot, continuous pilot and edge pilot in order to estimate the pilot patterns in accurate manner. Efficient channel frequency response and channel impulse response estimation is done in our proposed work by orthogonal property analysis. Finally, the proposed work simulation results evaluation yields high end performance when compare to the conventional works such as multi input-single output OFDM system.